Narrative Stimulating Cubes: A Qualitative Method for Analyzing the Nature of Democratic Culture among Hungarian Students (Szociológiai Szemle, 2023)
Several recent studies on youth culture have demonstrated the low participation and political radicalization of young adults. In an attempt to understand whether apathy, love of comfort or inactivity lies behind the low participation of young adults, the Campus-life project (http://campuslet.unideb.hu) aimed to identify factors that structure and organize students’ lives beyond the formal agents of civic socialization. Within this framework this paper seeks to reveal the relationship between public values and forms of collective action in two halls of residence at the University of Debrecen. In order to explore the forms of civic and political activities at the university a mixed method with the combination of quantitative and qualitative methods was employed. This paper, however, focuses its attention only on a specific projective technique used as a story trigger and presents an analysis of forty (4 semi-structured, 26 group and 10 narrative) interviews. The argument advanced in this paper is in accordance with Utasi’s findings that pointed to a process of the individualization of private communities in parallel with growing institutional individualization. This process can be characterized by the fact that, under the circumstances of increasing institutional dependency and control, individuals paradoxically avoid integrating into macro groups and advocate for career opportunities. This new form of generational orientation leads to new forms of civic and political involvement.